2014
DOI: 10.1257/aer.104.6.1551
|View full text |Cite
|
Sign up to set email alerts
|

Tenure, Experience, Human Capital, and Wages: A Tractable Equilibrium Search Model of Wage Dynamics

Abstract: Our main objective in this paper is to quantify the relative importance of human capital accumulation and imperfect labor market competition in shaping individual labor earnings profiles over the working life. We contribute to the empirical literature on wage equations along three broad dimensions.The first one relates to Mincer's (1974) original specification of log-earnings as a function of individual schooling and experience. In their review of Mincer's stylized facts about postschooling wage growth in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(60 citation statements)
references
References 44 publications
1
59
0
Order By: Relevance
“…In an influential study, Topel and Ward (1992) found that the wage increases that employees experience when moving to new employers account for more than one-third of the wage growth during the first decade of the working life of white men in the United states. 1 Using a structural estimation of an equilibrium search model with Danish data similar to ours, bagger, Fontaine, Postel-Vinay, and Robin (2014) concluded that job searches explain a large part of the wage growth early in a career and that it drives most of the wage dynamics afterward. The mechanism leading to earnings growth in this model is similar to the one in Postel-Vinay and Robin (2002), in which firms do not commit to long-term wage growth but, instead, renegotiate the worker's piece rate each time he or she obtains an attractive outside offer.…”
mentioning
confidence: 66%
“…In an influential study, Topel and Ward (1992) found that the wage increases that employees experience when moving to new employers account for more than one-third of the wage growth during the first decade of the working life of white men in the United states. 1 Using a structural estimation of an equilibrium search model with Danish data similar to ours, bagger, Fontaine, Postel-Vinay, and Robin (2014) concluded that job searches explain a large part of the wage growth early in a career and that it drives most of the wage dynamics afterward. The mechanism leading to earnings growth in this model is similar to the one in Postel-Vinay and Robin (2002), in which firms do not commit to long-term wage growth but, instead, renegotiate the worker's piece rate each time he or she obtains an attractive outside offer.…”
mentioning
confidence: 66%
“…The variables I include in the propensity score are selected by drawing on previous empirical work studying the determinates of union membership, wages, and the union wage premium (e.g., among others, Lewis ; Abraham and Farber ; Altonji and Shakotko ; Wunnava and Ewing ; Bryson ; Oi and Idson ; Galarneau and Sohn ; Lemieux ; Cornelißen and Hübler ; Bagger et al. ) as well as theoretical considerations and include demographic factors (age, gender, marital status, educational attainment), job characteristics (whether the job is permanent, industry), controls for firm (establishment) size, job tenure, and province dummies. I also estimate the union wage premium disaggregating the data by gender and for these analyses I do not include the gender dummy in the propensity score.…”
Section: Empirical Approachmentioning
confidence: 99%
“…To make the analysis tractable, I consider that (1) firms post a skill price θOitaliced for each skill group italiced subject to the constraint that health ht cannot be priced, which determines wage, and (2) they decide whether to offer ESHI to all of their workforce Ofalse{0,1false}. The assumption of skill price posting follows the literature of empirical search models with worker heterogeneity (e.g., Barlevy (), Bagger et al (), and Taber and Vejlin ()), which discuss its empirical plausibility , . The assumption that firms cannot condition on individual health is made either because worker health status is not observed by firms or because many labor regulations limit firm's ability to condition on hiring, firing, and compensation based on an individual's health status , , .…”
Section: Modelmentioning
confidence: 99%
“…This paper considers that the sector choice (ESHI or not) is affected by labor market sorting. Recently, Bagger, Fontaine, Postel‐Vinay, and Robin () and Lise and Postel‐Vinay () estimated equilibrium search models with sorting and endogenous skill accumulation. This paper contributes to the literature by investigating how workers with different skills and health sort themselves into jobs with multidimensional compensation packages over the life cycle, its implications for firms' choice of compensation packages, and how to design public policies when labor market sorting is crucial…”
Section: Introductionmentioning
confidence: 99%